Palmitic Amide Triggers Virus Life Cycle via Enhancing Host Energy Metabolism - Zhang, Xinyi; Zhuang, Jianjian; Huang, Liquan; Zhang, Xiaobo (Frontiers in Microbiology, 2022)
Viruses contribute to the mortality of organisms, consequentially altering biological species composition of an ecosystem and having a threat on human health. As the most famous model for the initiation of virus infection, the Hershey-Chase experiment has revealed that on infection, the bacteriophage genomic DNA is injected into its host bacterium, while the viral capsid is left on the outer membrane of host cell. However, little is known about the injection of any other materials into the cytoplasm of host cells along with genomic DNA to trigger the virus life cycle. In this study, the results showed that palmitic amide packaged in the virions of GVE2, a bacteriophage infecting deep-sea hydrothermal vent thermophile Geobacillus sp. E263, promoted virus infection. Palmitic amide was interacted with acetate kinase to increase its enzymatic activity, thus enhancing the acetate-mediated energy metabolism. Furthermore, palmitic amide promoted tricarboxylic acid cycle (TCA cycle) to support virus infection. These data indicated that palmitic amide, packaged in the virions, might serve as a second messenger at the initiation step of virus infection by enhancing the host energy metabolism. Therefore our study revealed a novel mechanism for the initiation of the virus life cycle.